To Study Island China - Zuan Ou; Shuangjuan Zhan; Ping Su; Adam Grydehøj (Island Studies Journal, 2024)
As greater attention has been paid to island research in China, interactions between Chinese and international island scholars have increased. However, research has tended to take an ‘islands of China’ approach, which perceives China as a continental country surrounded by a large number of islands. The present paper proposes an alternative ‘island China’ perspective, informed by selected Chinese traditions of thinking about islands and the sea, that captures the role islands have played and continue to play in Chinese culture. Drawing upon Fei Xiaotong’s reflexive concept of ‘cultural self-consciousness’, we consider the cultural history of island China, including conceptual tensions between the binaries of continent/island and center/periphery, conceptions of land dwellers and water dwellers, the role of islands as hubs of cultural transmission, and the formation of maritime societies across East and Southeast Asia. We also argue that this cultural history ought to influence island governance in China today.